Undescended Testes. Microvascular Surgery - de Vecchi (h), Jorge; Cepellini, Raúl; Torres, David; Arruti, César; Ravera de Bengochea, Diva; Wettstein, Juana María; Lesina, Elmer; Anavitarte, Eduardo (Cirugía del Uruguay, 1980)
Case of undescended testes treated by microvascular surgery is reported. The authors anasto·mose the spermatic vessels tothe epigastric artery and vein.